Mathematical Simulation of Forest Fuel Pyrolysis and Crown Forest Fire Impact for Forest Fire Danger and Risk Assessment; Processes; Vol. 10, iss. 3 - Baranovskiy N. V. Nikolay Viktorovich (2022, 2022)
Title screen